Pengaruh Model Pembelajaran Berbasis Masalah (PBM) terhadap Keterampilan Pemecahan Masalah dan Hasil Belajar Kognitif Siswa Kelas VIII - Mulyani, Fita (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The aim of this study was to determine the effect of Problem-Based Learning (PBM) on problem-solving skills and cognitive learning outcomes of class VIII MTs students. Hidayatullah academic year 2016/2017. The type of research used in this research is Quasi Experiment. The research design in this study was Randomized Control Group Only Design and the research sample was class VIII A as many as 19 people as the experimental class and class VIII B as many as 13 people as the control class. Data collection used observation sheets to determine problem solving skills, test sheets to determine cognitive learning outcomes. The results of the study showed that the implementation of the RPP on cognitive learning outcomes with the percentage of implementation of experimental class learning at the 1st meeting was 70%, the 2nd meeting was 90% and in the control class the 1st meeting was 50%, the 2nd meeting was 70% . Based on data analysis, it was obtained that the value of the experimental class for problem solving skills at the 1st meeting was 50% in the medium category, the 2nd meeting was 83.33% in the very high category, the control class in the 1st meeting was 33.33% in the low category , the second meeting was 66.6% in the high category. The average value of the experimental class for pretest cognitive learning outcomes was 45, with the highest score being 55, while the lowest score was 35, the post-test average score was 78.9, with the highest score being 95, while the lowest score was 60, while the class control pretest average value of 39.6, with the highest value of 50, while the lowest value is 25, while the post-test average value is 64.4, while the highest value is 80, the lowest value is 45. Hypothesis test used the analysis t-test at a significant level of 5% obtained a tcount of 4.18, the value is larger than the t-table value of 2.042, which means that Ho is rejected and Ha is accepted. It can be concluded that there was an influence of the Problem Based Learning (PBM) model on problem solving skills and cognitive learning outcomes of class VIII MTs students of Hidayatullah academic year 2016/2017.